Analisis Rasio Solvabilitas Untuk Mengukur Kinerja Keuangan Pada Bank SulutGo - Runtuwene, Aditya; Pelleng, Frendy A. O.; Manoppo, Wilfried S. (Sam Ratulangi University, 2019)
This study aims to determine the financial performance based on Bank Sulut Go's solvency ratio. In this study quantitative descriptive research was used. Data collection techniques using documentation techniques, namely data obtained from documents in the form of financial statements of North Sulawesi Bank in 2014-2018. The analysis technique used is bank solvency ratio analysis consisting of Capital Ratio, Primary Ratio, Risk Assets Ratio, Secondary Risk Ratio, and Capital Adequacy Ratio. Based on the results obtained that the primary ratio, risk assets ratio, capital ratio, and capital adequacy ratio that pay attention to fixed assets, as well as PT Bank SulutGo capital adequacy ratio in 2014 - 2018 shows a trend of increasing. The minimum level of capital provision for Bank SulutGo is fulfilled from 2014 to 2018 in accordance with regulations concerning changes to Bank Indonesia Regulation Number: 7/15 / PBI / 2005 concerning the number of core capital of commercial banks which requires CAR to be at least 8%.